Comments on the type specimens of Lindsaea andamanica (Lindsaeaceae) at Central National Herbarium (Cal), India (Bangladesh Journal of Plant Taxonomy, 2009)
Not available.Keywords: Corrections; Lindsaea andamanica; Type specimens. DOI: 10.3329/bjpt.v16i2.3930 Bangladesh J. Plant Taxon. 16(2): 175-176, 2009 (December)